Engineering chemistry - Maheswaramma, K. Sesha; Chugh, Mridula (Always learning., 2016)
Designed for the course on Engineering Chemistry offered to first year undergraduate students of engineering, this book aims to strengthen fundamental concepts and highlight the applications of chemistry in the field of engineering. Written in a simple and lucid manner, this book covers a broad spectrum of topics including water technology, alternate energy resources, science of corrosion and green chemistry. It also includes a large number of end-of-chapter exercises, which test student understanding and are also a valuable resource from the examination point of view.